Enforcement of law and order on the high seas : a legal analysis - Nicholson, Antony (Department of Civil Law, International Islamic University Malaysia, 2013)
The high seas refer to the open sea which is beyond the national jurisdiction of States, that is, beyond the 200 nautical mile limit of the Exclusive Economic Zones of coastal States. The high seas are open to all States and shall be reserved for peaceful purposes. All States have the right of navigation on the high seas and every State has the right to sail ships flying its flag on the high seas. The legal status of the high seas is regulated by the United Nations Convention on the Law of the Sea 1982 (UNCLOS) and by international law. Ships sailing on the high seas are subject to the exclusive jurisdiction of the flag State save in exceptional cases provided for in the UNCLOS or in international treaties. However, in the interests of the maintenance of law and order on the high seas, international law allows certain exceptions to this general principle of the flag State‟s exclusive jurisdiction over its ships on the high seas, where other States share legislative and enforcement jurisdiction with the flag State. This study evaluates the laws relating to the high seas and examines the effectiveness of the enforcement of law and order on the high seas by the flag States and the other States based on the provisions of the UNCLOS and other rules of international law.